Study guides

☆☆

Q: 1 2 of a number m?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

mn = 80 m -n = -79 Substitute m - 80/m = -79 m^2 - 80 = -79m m^2 + 79m = 80 (NB Notice change of signs) Quadratic Eq'n m = { - 79 +/- sqrt[)79)^2 - 4(1)(-80)}] / 2(1) m = { - 79 +/- sqrt[6241 + 320}]/ 2 m = { -79 +/- sqrt[6561]} / 2 m = { - 79 +/- 81}/2 m = -160 / 2 = -80 or m = 2/2 = 1 Hence n = 1 + 79 = 80

m={1-[fc/f(infinity)]}^(1/2)fc={1/[Lc]^(1/2)} f(infinity)={fc/[(1-m^2)^(1/2)]}

Yes --------------------------------------------- Let n be an integer. Then 2n is an even number Let m be an integer. Then 2m is an even number and 2m + 1 is an odd number. Then: even + odd = (2n) + (2m + 1) = (2n + 2m) + 1 = 2(n + m) + 1 = 2k + 1 (where k = m + n) which is an odd number.

m-2+1-2m+1 When simplified: -m

An odd number can be written in the form '2n+1' where 'n' is an integer, and an even number can be written int the form '2n'. We can then write the sum of 2 odd numbers as: (2n+1) + (2m+1) * Combining and factoring out a 2, we arrive at: 2(n + m + 1) Since 'n' and 'm' are both integers, we know that the value contained int the '()' is also an integer. We can therefore rewrite this equation to be: 2n Which represents an even number as given previously. * 'm' is an integer

Related questions

It is ((2^h) -1)/(2-1) generally for an m-tree is: ((m^h)-1)/(m-1)

df = (n-1)*(m-1) = (2-1)*(2-1) = 1*1 = 1

Suppose x is an even number and y is an odd number. Then x = 2*n for some integer n and y = 2*m + 1 for some integer m Therefore x + y = 2*n + 2*m + 1 = 2*(n + m) +1 Now, since n and m are integers, (n + m) is also an integer [by the closure of integers under addition]. Thus, x + y = 2*p + 1 where p = n + m is an integer. ie x + y is an odd integer.

(m-2)/(m+2) * m/(m-1) = [(m-2)*m]/[(m+2)*(m-1)] = (m2 - 2m)/m2 + m - 2)

2 1/2 tons

To find the (mean) average, add all the numbers and divide by the number of numbers. The sum of a series of digits (in arithmetic progression, like 13, 14, 15, ... 37) is sum = (first + last) x number_of_digits / 2 So their average is: average = ((first + last) x number_of_digits / 2) / number_of_digits = (first + last) / 2 = average of first and last digits! So the average of the numbers 13, 14, 15, ..., 37 is: average = (13 + 37) / 2 = 50 / 2 = 25 To find the sum of n digits starting with m: Sum = m + (m+1) + ... + (m+n-2) + (m+n-1) Rewrite the sum in reverse order: Sum2 = Sum = (m+n-1) + (m+n-2) + ... + (m+1) + m Add the two sums, term by term: Sum + Sum2 = 2 Sum = (m + (m+n-1)) + (m + (m+n-1)) + ... + (m + (m+n-1)) + (m + (m+n-1)) There are n terms, all (m + (m+n-1)), so: 2 Sum = (m + m+n-1) x n Sum = (m + m+n-1) x n / 2 But n is the number of digits, m is the first number and (m+n-1) is the last, so: Sum = (first + last) x number_of_digits / 2

mn = 80 m -n = -79 Substitute m - 80/m = -79 m^2 - 80 = -79m m^2 + 79m = 80 (NB Notice change of signs) Quadratic Eq'n m = { - 79 +/- sqrt[)79)^2 - 4(1)(-80)}] / 2(1) m = { - 79 +/- sqrt[6241 + 320}]/ 2 m = { -79 +/- sqrt[6561]} / 2 m = { - 79 +/- 81}/2 m = -160 / 2 = -80 or m = 2/2 = 1 Hence n = 1 + 79 = 80

n=3 l=2 m=-1 s =-1/2

Suppose x is an odd number, then x leaves a remainder when divided by 2. That is, x = 2m+1 (for some integer m). Suppose y is an even number, then y is a multiple of 2 so suppose y = 2n (for some integer n). Then x-y = 2m+1 - 2n = 2m-2n + 1 =2(m-n) + 1 Since m and n are integers, then m+n is an integer so that the sum gives 1 more than a multiple of 2. And that is what an odd number is!

m/2

1 mm = 1/1000 m → 1 mm × 2 m = 1 × 1/1000 m × 2 m = 0.002 m² Or 1 m = 1000 mm → 1 mm × 2 m = 1 mm × 2 × 1000 mm = 2000 mm²

-m2+3m-2 -m2+2m+m-2 -m(m -2)+1(m-2) (-m+1)(m-2) or

People also asked